In Vitro Anti-Inflammatory, Lipoxygenase, Xanthine Oxidase And Acetycholinesterase Inhibitory Activity Of Tecoma Stans (L.) Juss. Ex Kunth - GOVINDAPPA M; SADANANDA TS; CHANNABASAVA R; VINAY B. RAGHAVENDRA (International Journal of Pharma and Bio Sciences, 2011)
The ethanol, methanol and water extracts of Tecoma stans effective against tested for anti-inflammatory activity, lipoxygenase, xanthine oxidase and acetycholinesterase inhibitory activity. The methanol, ethanol and water extracts showed in vitro anti-inflammatory activity by inhibiting the heat induced albumin denaturation is 86.32, 83.81, 61.39 g/ml and red blood cells membrane stabilization with 71.29, 67.78, 54.48 g/ml respectively. Proteinase activity was also significantly inhibited by the methanol (83.91), ethanol (81.88) and water (61.73). In addition, the methanol and ethanol extracts showed anti-lipoxygenase activity range from 39.32-58.92. The study also showed that methanol and ethanol fractions exhibited a moderate xanthine oxidase inhibitory activity comparatively to the acetylcholinestearse which was weakly inhibited by the tested extracts. The results obtained in the present investigation indicate that methanol and ethanol extracts of T. stans can be a potential source of anti-inflammatory agents.